MAJA: A two-region DSGE model for Sweden and its main trading partners - Vesna Corbo; Ingvar Strid (Sveriges Riksbank, 2020)
The Swedish economy is strongly dependent on global economic developments, which is re‡ected in generally strong empirical relationships between Swedish and foreign macroeconomic variables. It is, however, diffi cult for standard open-economy dynamic stochastic general equilibrium (DSGE) models to generate substantial cross-country spillovers; see e.g. the seminal paper of Justiniano and Preston (2010). We present a two-region DSGE model that better captures the dependence on global economic developments than previous models. It is estimated on data for Sweden and an aggregate of its main trading partners, the euro area and the United States, for the period 1995Q2-2018Q4. To capture the strong empirical relationships between Sweden and the foreign economy, we assume that global shocks to e.g. technology, real interest rates, financial risk, and firm and consumer sentiment directly affect both economies, while their impact on each economy may differ. We also allow for a ‡exible specification of the demand for Swedish exports to better account for the ‡uctuations in Swedish trade. Finally, headline and core in‡ation are distinguished by the introduction of consumption of energy goods, which allows for a more detailed and realistic analysis of in‡ation developments. This new model, named MAJA (Modell för Allmän JämviktsAnalys), is used by the Riksbank for interpretation of economic developments, forecasting, scenarios, and policy analysis. It builds on the work of Christiano, Eichenbaum, and Evans (2005) and Smets and Wouters (2003) and the Riksbank's previous models, Ramses I and Ramses II (see Adolfson et al. (2007) and Adolfson et al. (2013), respectively).
Keywords: E30; E40; E37; E52; F41; F44; C11; C32; C52; 330; DSGE model; Monetary Policy; Open economy; International spillovers; Bayesian estimation